Necrotizing fasciitis with prior leprosy: a case report - Teng, Vannia C.; Esti, Prima K.; Pribadi, Sweety (International Journal of Research in Dermatology, 2020)
Necrotizing fasciitis (NF) is a life-threatening soft tissue infection with a high misdiagnosis rate. Here, we present the case of NF with hypoesthesia due to prior leprosy in a limited resource area. Laboratory risk indicator for NF (LRINEC) score was used to determine the diagnosis of NF. Resuscitation and broad-spectrum antibiotic were initiated, followed by surgical debridement due to lack of wound improvement and skin graft to cover the wound was done. This case report highlights the usage of LRINEC score to reduce misdiagnosis, ensure early diagnosis, and improve patient management in NF with masking effect.